Research on 3D Measurements used for Archaeological Materials in Japan - Nakagawa, Tomomi (The Indonesian Journal of Social Studies, 2024)
This study reviews our research in Japan on examining the 3D measurement method and the accuracy of 3D models. Recently, 3D measurements and the data have been used in various archaeological situations (e.g., recording at excavations, preservation, repairs, education, and research analysis). In particular, SfM/MVS photogrammetry has received increasing attention because it is versatile and inexpensive. However, there are some issues. First, a systematical way to construct 3D model by SfM/MVS photogrammetry has not been established yet, even though various conditions can be set. Considering the sustainability and convenience of 3D data in the future, it is preferable to investigate the degree of effect on 3D model in different conditions and settings (e.g., the number of photos, the kind of camera, the photographing setting of cameras). Second, while archaeologists have classified relics by detail types, there still is a lack of verification between methods. Third, the analysis results of 3D data and previous studies should be compared. We measured and compared one style of jar (Ongagawa style) and human skeletal remains by SfM/MVS and used laser measurement to resolve the first and second issues. We first compared the same materials measured under different cameras conditions and settings. Having applied the SfM/MVS methods of this study, there was only a small difference in the quality of models created by the different methods. Second, we compared the SfM/MVS models with laser models. The result was that the differences between models are little, which shows that SfM/MVS models, under certain conditions, are not inferior to laser measurement models.